Development of Vibration Based Optical Fiber Sensor for Tremor Measurement - Anuar, Nurul Amirul; Wan Zaki, Wan Suhaimizan (Evolution in Electrical and Electronic Engineering, 2025)
Parkinson’s disease is a neurological disorder characterized by involuntary tremors affecting various parts of the body. The condition can result from dysfunction in specific regions of the brain, as well as factors such as incorrect medication, drug use, and alcohol consumption. Existing diagnostic tools for Parkinson’s-related tremor analysis often have high costs, bulky designs, and limited comfort, which can restrict natural hand movement and reduce user compliance. This project proposes a compact, low-cost tremor measurement system using a fiber optic sensor to detect tremors in the hand or finger, particularly in individuals with Parkinson’s disease. The thin and flexible nature of fiber optics allows for accurate tremor measurement while enabling a wider range of natural hand movements. An MPU6050 accelerometer is also integrated to provide comparative motion data. Arduino Uno is used for data acquisition, while MATLAB is employed for real-time signal processing, frequency analysis, and visualization. Preliminary results are expected to show that the system can accurately measure tremor amplitude and frequency within the range typically observed in resting Parkinson’s patients which is 4–6 Hz. Comparative analysis between the fiber optic and accelerometer measurements will validate the reliability and accuracy of the proposed method. The outcome of this project is a portable diagnostic tool suitable for early detection, ongoing monitoring, and quantitative assessment of Parkinson’s disease in both clinical and home-based settings.